Antioxidant Potential of Epigallocatechin-3-gallate, Ascorbic Acid, and Sodium Ascorbate in Solution and Gel Forms by 2,2-diphenyl-1-picrylhydrazyl (DPPH) Assay - Virdah Dwi Dewaantari; Setyabudi Setyabudi; Kun Ismiyatin (Universitas Airlangga, 2021)
Background: Free radicals are molecules without any electron pairs, unstable, and highly reactive. Antioxidants are needed to reduce free radicals. Antioxidants provide various benefits in dentistry as a preventive agent for caries, healing, bone formation, mouthwash, preventive and therapeutic cancer, and reduction of periodontal disease progressions. Additionally, research on antioxidants is still undergone due to the existence of free radical residues on bleached teeth. Epigallocatechin-3-gallate (EGCG), ascorbic acid (AA), and sodium ascorbate (SA) are ingridients that have antioxidant properties. Antioxidants can be in two forms solution and gel. Solutions have a higher substance releasing power than gel. Gel is extremely adhesive, so it does not flow easily. Meanwhile, solutions are rather unstable because it flows easily. Antioxidant activities were evaluated with 2,2-diphenyl-1-picrylhydrazyl (DPPH) Assay method. Purpose: Analyzing through literature reviews the potential antioxidants of EGCG, AA, and SA in solution and gel forms by DPPH Assay. Reviews: There were eight journal articles used in this review. The first article described antioxidant solutions in which EGCG was higher than sodium ascorbate. The second article showed that antioxidant gel EGCG was lower than sodium ascorbate. The third journal explained that ascorbic acid was higher than sodium ascorbate both in solution and gel forms. The other articles provided some information about the antioxidant activity percentages of EGCG, SA, and AA in the forms of gel and solutions by DPPH assay. Conclusion: EGCG has a higher antioxidant activity than SA, but it is lower when compared to AA in both solution and gel forms by DPPH assay.